2010
DOI: 10.1021/ie1009537
|View full text |Cite
|
Sign up to set email alerts
|

New Apparatus for Solubility Measurements of Solids in Carbon Dioxide

Abstract: The aim of this work is to present a new experimental apparatus based on the static-analytic method suitable to perform solubility measurements of solids in sub- and supercritical carbon dioxide. Mole fractions of dissolved solids are determined online via high-performance liquid chromatography. The studied binary mixtures are capsaicin in carbon dioxide from 298 to 328 K, hexadecanoic acid in carbon dioxide at 313 and 318 K, β-carotene in carbon dioxide at 298 and 313 K, and acetaminophen in carbon dioxide at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…In order to eliminate errors associated with sample collection and sample preparation stages required for off-line analysis, several reports have described the use of static SF-CO 2 solubility apparatus coupled online with spectroscopy or chromatography. To perform online spectroscopic measurements, the supercritical solubility vessel (SSV) is equipped with high pressure inspection windows that facilitate UV/vis, IR, or fluorescence analysis. , Several reports have described the use of a SSV directly coupled online with HPLC to perform static solubility measurements. The development of these techniques involves using a mobile phase with high organic modifier content to prevent gas bubbles derived from decompressed injections of SF-CO 2 samples interfering with the stability of the HPLC detector . We have previously reported the development of a two-valve interface to monitor the progress of an esterification reaction conducted in SF-CO 2 using online HPLC .…”
Section: Introductionmentioning
confidence: 99%
“…In order to eliminate errors associated with sample collection and sample preparation stages required for off-line analysis, several reports have described the use of static SF-CO 2 solubility apparatus coupled online with spectroscopy or chromatography. To perform online spectroscopic measurements, the supercritical solubility vessel (SSV) is equipped with high pressure inspection windows that facilitate UV/vis, IR, or fluorescence analysis. , Several reports have described the use of a SSV directly coupled online with HPLC to perform static solubility measurements. The development of these techniques involves using a mobile phase with high organic modifier content to prevent gas bubbles derived from decompressed injections of SF-CO 2 samples interfering with the stability of the HPLC detector . We have previously reported the development of a two-valve interface to monitor the progress of an esterification reaction conducted in SF-CO 2 using online HPLC .…”
Section: Introductionmentioning
confidence: 99%
“…1,7,8,11,13−15 Pereira et al 7 measured VLLE at temperatures from 292.15 to 304.25 K and determined the upper critical end point (UCEP) at 304.25 K for the system CO 2 + α-tocopherol. Pereira et al, 7 Meier et al, 8 Moser and Trepp, 11 Chen et al, 13 S ̂kerget et al, 14 and Fang et al 15 reported VLE for this system at temperatures from 298.1 to 402 K. Regarding solubilities of capsaicin in supercritical carbon dioxide, these have been reported by Knez and Steiner, 16 Hansen et al, de la Fuente et al, 18 Elizalde-Solis and Galicia-Luna, 19,21 and Valderrama et al 20 Meanwhile, solubilities of palmitic acid have been extensively reported by different authors: Ohgaki et al, 2 Kramer and Thodos, 22 Bamberger et al, 23 Iwai et al, 24 Maheshwari et al, 25 Cho et al, 26 Noh et al, 28 Gordillo et al, 29 Garlapati and Madras, 30,31 Brandt et al, 32 Elizalde-Solis and Galicia-Luna, 21 and Rosales-Garci ́a et al 33 These authors covered measurements at temperatures from 298 to 338 K. Bharath et al 27 reported the presence of VLE for the system CO 2 + palmitic acid at higher temperatures of 353.15 and 373.15 K.…”
Section: ■ Introductionmentioning
confidence: 65%
“…Extraction of phenolic fraction from guava seeds (Psidium guajava L.) using supercritical carbon dioxide and co-solvents 2010 [180] Extraction of pesticides from soil using supercritical carbon dioxide added with methanol as co-solvent 2012 [181] Design and analysis of antioxidant compounds from Andes Berry fruits (Rubus glaucus Benth) using an enhanced-fluidity liquid extraction process with CO 2 and ethanol 2012 [182] Extraction of oil from chia seeds with supercritical CO 2 2011 [183] Guava (Psidium guajava L.) seed oil obtained with a homemade supercritical fluid extraction system using supercritical CO 2 and co-solvent 2011 [184] Lippia origanoides chemotype differentiation based on essential oil GC-MS and principal component analysis 2011 [185] Integrated utilization of guava (Psidium guajava l.): antioxidant activity of phenolic extracts obtained from guava seeds with supercritical CO 2 -ethanol 2011 [186] Extraction of phenolic fraction from guava seeds (Psidium guajava L.) using supercritical carbon dioxide and co-solvents 2010 [180] Separation of fractions from vacuum residue by supercritical extraction 2010 [187] Reacting flow simulations of supercritical water oxidation of PCB-contaminated transformer oil in a pilot plant reactor 2011 [188] Reactions in supercritical fluids Biodiesel fuels through a continuous flow process of chicken fat supercritical transesterification 2010 [189] On the center of mass velocity in molecular dynamics simulations 2012 [190] [192] Solubility of mesquite gum in supercritical carbon dioxide 2011 [193] New apparatus for solubility measurements of solids in carbon dioxide 2011 [194] Loci of extrema of thermodynamic response functions for the Lennard-Jones fluid 2011 [195] Solubility and density measurements of palmitic acid in supercritical carbon dioxide plus alcohol mixtures 2010 [196] Material and micronization applications…”
Section: Analytical Applicationsmentioning
confidence: 99%